Endoscopic ultrasound guided gastrojejunostomy - Dawod, Enad; Nieto, Jose M. (Translational Gastroenterology and Hepatology, 2018)
Endoscopic ultrasound guided gastrojejunostomy (EUS-GJ) has been mostly employed in the treatment of benign and malignant gastric outlet obstruction (GOO). Additionally, EUS-GJ has been used in the treatment of afferent loop syndrome. EUS-GJ has been employed in the treatment of benign and malignant GOO. EUS-GJ has also been used in the treatment of afferent loop syndrome. EUS-GJ involves obtaining access to the jejunum endoscopically and sonographically from the stomach, using a biflanged lumen apposing metal stent (LAMS). This is achieved through a newly formed fistulous tract. Thus creating a gastrojejunal bypass fully endoscopically. Several techniques have been described in preforming EUS-GJ but no method has been shown to be superior. In afferent loop syndrome initial data show high technical and clinical success rates and decreased need for reintervention. With malignant GOO, data available from the limited number of studies conducted demonstrated he superiority of EUS-GJ when compared to standard enteral stenting in terms of decreasing recurrence of GOO and need for reintervention. With benign GOO, EUS-GE offers a solution to the long-term patency and recurrence issue encountered with enteral stenting and endoscopic balloon dilation. EUS-GJ offers a less invasive approach than surgery for the treatment of several etiologies, giving the patients the option to avoid adverse events associated with surgery.